A novel Li4Ti5O12-based high-performance lithium-ion electrode at elevated temperature1. Issue 9 (7th March 2015) - Guo, Junling; Zuo, Wenhua; Cai, Yingjun; Chen, Shimou; Zhang, Suojiang; Liu, Jinping
<x xml:space="preserve">Abstract</x> A Li4Ti5O12-based nanowire array electrode that can be cycled at elevated temperature (60 °C; 500 cycles) has been constructed.